Direct Experimental Evidence for Halogen–Aryl π Interactions in Solution from Molecular Torsion Balances. (28th April 2017) - Sun, Han; Horatscheck, André; Martos, Vera; Bartetzko, Max; Uhrig, Ulrike; Lentz, Dieter; Schmieder, Peter; Nazaré, Marc
Abstract: We dissected halogen–aryl π interactions experimentally using a bicyclic N‐arylimide based molecular torsion balances system, which is based on the influence of the non‐bonded interaction on the equilibria between folded and unfolded states. Through comparison of balances modulated by higher halogens with fluorine balances, we determined the magnitude of the halogen–aryl π interactions in our unimolecular systems to be larger than −5.0 kJ mol −1, which is comparable with the magnitude estimated in the biomolecular systems. Our study provides direct experimental evidence of halogen–aryl π interactions in solution, which until now have only been revealed in the solid state and evaluated theoretically by quantum‐mechanical calculations.